2018
DOI: 10.1037/aca0000099
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the relationship between intelligence and visual “taste” measures.

Abstract: What makes individuals experts in judging aesthetic value is actively researched in a variety of ways. In the visual domain, one classical paradigm-used in "T" (for Taste) tests (Eysenck, 1983)-consists in comparing one's evaluative judgments of beauty with a standard judgment-provided by consensual or expert agreement. The association between general intelligence (g) and performance in "T" tests has been investigated since over 70 years (Eysenck, 1940;Myszkowski, Storme, Zenasni, & Lubart, 2014), but has led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 80 publications
(169 reference statements)
0
27
0
Order By: Relevance
“…The VAST was designed intending to overcome the psychometric problems common to earlier design and art judgement tests that presented participants with pairs of correct and incorrect alternatives (e.g., the Graves Design Judgment Test, Graves, ; or the Meier–Seashore Art Judgment Test, Meier & Seashore, ). The fact is, however, that like the tests it intended to surpass, the VAST exhibits low internal consistency and structural validity, and its scores are explained by intelligence, figural creativity, and personality traits such as conscientiousness, extraversion, or openness to experience (Chamorro‐Premuzic & Furnham, ; Furnham & Chamorro‐Premuzic, ; Myszkowski, Çelik, & Storme, ; Myszkowski, Storme, Zenasni, & Lubart, ). Contrary to Eysenck's (1941a, ) claims, thus, this notion of aesthetic sensitivity appears not to be a distinct ability.…”
Section: Introductionmentioning
confidence: 99%
“…The VAST was designed intending to overcome the psychometric problems common to earlier design and art judgement tests that presented participants with pairs of correct and incorrect alternatives (e.g., the Graves Design Judgment Test, Graves, ; or the Meier–Seashore Art Judgment Test, Meier & Seashore, ). The fact is, however, that like the tests it intended to surpass, the VAST exhibits low internal consistency and structural validity, and its scores are explained by intelligence, figural creativity, and personality traits such as conscientiousness, extraversion, or openness to experience (Chamorro‐Premuzic & Furnham, ; Furnham & Chamorro‐Premuzic, ; Myszkowski, Çelik, & Storme, ; Myszkowski, Storme, Zenasni, & Lubart, ). Contrary to Eysenck's (1941a, ) claims, thus, this notion of aesthetic sensitivity appears not to be a distinct ability.…”
Section: Introductionmentioning
confidence: 99%
“…Eysenck's VAST (Götz et al, 1979) was conceived to provide a valid and reliable measure of aesthetic sensitivity. Recent studies, however, revealed the VAST's psychometric weaknesses (Myszkowski et al, 2018;Myszkowski & Storme, 2017;Myszkowski et al, 2014;Myszkowski & Zenasni, 2016). Contrary to Eysenck's conception, aesthetic sensitivity as measured with the VAST is not a distinct ability: It is related to general intelligence, certain personality traits, and certain aspects of creativity (Myszkowski et al, 2018;Myszkowski et al, 2014).…”
Section: Discussionmentioning
confidence: 86%
“…Recent studies, however, revealed the VAST's psychometric weaknesses (Myszkowski et al, 2018;Myszkowski & Storme, 2017;Myszkowski et al, 2014;Myszkowski & Zenasni, 2016). Contrary to Eysenck's conception, aesthetic sensitivity as measured with the VAST is not a distinct ability: It is related to general intelligence, certain personality traits, and certain aspects of creativity (Myszkowski et al, 2018;Myszkowski et al, 2014). In addition to these measurement problems, Eysenck's notion of aesthetic sensitivity stands upon premises that have been rendered invalid with advances in neuroscience and psychology in general and empirical aesthetics in particular (Skov & Nadal, 2018).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Notably, Eysenck introduced confusion by originally discussing the construct as intelligence in the aesthetic domain (1940) to then speculate that the construct should be independent from intelligence (Frois and Eysenck, 1995)-which is contradicted in a recent meta-analysis (Myszkowski et al, 2018), which showed across 23 studies that its correlation with intelligence is significant and around 0.30. Nevertheless, one can reasonably expect that, as is found empirically, visual aesthetic sensitivity would be positively correlated with intelligencebecause common cognitive processes are likely engaged in both measures (Myszkowski et al, 2018), and because it is common to observe relations between sensory perception in other domains and intelligence (e.g., Troche and Rammsayer, 2009)-or with personality traits like openness to aesthetics (Myszkowski et al, 2014)-because individuals with stronger interest in aesthetics may engage in more extensive processing, leading to higher accuracy, as it was for example found (Myszkowski, 2019) that, in these tests, response speed is negatively correlated with accuracy. Therefore, even though the nomological network of visual aesthetic sensitivity is not sufficiently (nor consistently) discussed, the pattern of relations between aesthetic sensitivity and other measures does suggest that visual aesthetic sensitivity measures present evidence of concurrent validity (Myszkowski et al, 2020).…”
Section: Elements Of Validity Of Visual Aesthetic Sensitivity Measuresmentioning
confidence: 99%